2000
DOI: 10.1111/j.1532-5415.2000.tb03877.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Proxy Respondents in Studies of Older Adults: Lessons, Challenges, and Opportunities

Abstract: Findings tend to support the use of proxy ratings among older adults in many areas but not all when self-reports are not feasible. There is a need for more evaluation of proxy data in relation to other measures, such as performance assessments, medical records, and claims data, which may be less subject to respondent biases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
185
3
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(206 citation statements)
references
References 41 publications
17
185
3
1
Order By: Relevance
“…26 However, the accuracy of information acquired by proxies -excluded herein by interviewing all probands -varies significantly according to the health area assessed by the telephone survey. 27,28 This could at least partly explain thedespite divergent ground populations -unexpected high discrepancy between the estimations of psoriasis prevalence in the elderly found with the same questionnaire in the present face-to-face interview and the former telephone survey study. 17 Furthermore, this observation underscores the difficulties in measuring skin-related morbidity of older probands by using proxies sources, and calls for research focusing on the evaluation of the quality of proxy informations in the area of geriatric dermatology.…”
Section: Discussionmentioning
confidence: 83%
“…26 However, the accuracy of information acquired by proxies -excluded herein by interviewing all probands -varies significantly according to the health area assessed by the telephone survey. 27,28 This could at least partly explain thedespite divergent ground populations -unexpected high discrepancy between the estimations of psoriasis prevalence in the elderly found with the same questionnaire in the present face-to-face interview and the former telephone survey study. 17 Furthermore, this observation underscores the difficulties in measuring skin-related morbidity of older probands by using proxies sources, and calls for research focusing on the evaluation of the quality of proxy informations in the area of geriatric dermatology.…”
Section: Discussionmentioning
confidence: 83%
“…Proxy reports provided by a family member, often the child of the patient, are frequently used as a measure of the health and well-being of older individuals (Schulz et al, 2013). Proxy reports are used most often when the individual's condition is severe and his or her health is very poor, or when a person has dementia (Neumann et al, 2000). Considering that a caregiver is often the one involved with medical decision-making, it is important to know how well a proxy report provided by a family member matches the health status of the person of interest, and what may influence a caregiver's likelihood of hiring an HCA for another person.…”
Section: Andersen-newman Model Of Healthcare Usementioning
confidence: 99%
“…The literature, however, is not unequivocal concerning the accuracy of proxy informants (Neumann, Araki, & Gutterman, 2000). For example, Kolanowski, Hoffman, and Hofer (2007) reported that the concordance of self-report and informant assessments of emotional well-being among nursing home residents was low.…”
mentioning
confidence: 99%
“…Data from personality assessments suggest that even though there are mean differences on some personality trait ratings, these differences are only in degree and not in substance (Martin, 2007). Neumann et al (2000) conducted a Medline review of 24 clinical studies that used proxy data and concluded that proxy-and subject reports are often comparable in describing level of functioning, overall health, chronic physical conditions, and physical symptoms. Schneider and Schimmack (2009) reported that self-informant agreement in wellbeing ratings was influenced by construct, age of the target participant, and number of items in the measure.…”
mentioning
confidence: 99%